(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2024)
Background: Restoration of enteral feeding is believed to enhance recovery after surgery, but intestinal anastomosis is a matter of apprehension for surgeons to start enteral feeding early. Before 2022, our standard practice was to wait three to four days to begin oral feeding after intestinal anastomosis. Since 2022, we have allowed oral feeding to start within 24 hours of intestinal anastomosis. This study compares the safety and benefits of early oral feeding after intestinal anastomosis in children. Methods: This retrospective study was done in the neonatal and paediatric surgery department, BSH&I, from January 2021 to December 2022. Children who received early oral feeding in 2022 compared with children who received oral feeding after three days in 2021. Children with duodenal anastomosis and anastomosis with a covering stoma were excluded. Demographic and clinical data were extracted from hospital records using a predefined questionnaire. Data were analyzed in SPSS 26, and a p-value <0.05 was considered significant. Results: One hundred thirty-three children (90 in 2022 and 43 in 2021) underwent intestinal anastomosis. Fiftynine (44.4%) children had small gut anastomosis, 62 (46.6%) children had large gut anastomosis, and 12 (9%) children had ileocolic anastomosis. There was no difference in gender and mean age at the surgery between the two groups. The mean time to start oral feeding was 19.9±0.59 hours in the case group and 79.1±13.9 hours in the control group (p<0.001). The mean time to full oral feeding was 61.05±4.5 hours in the case group and 125.67±25.51 hours in the control group (p<0.001). The mean hospital stay was 4.16±1.18 days in the case group and 7.06±1.96 days in the control group (p<0.001). The two groups had no significant differences in anastomotic and wound complications. Conclusion: Early oral feeding after intestinal anastomosis is safe in children and reduces postoperative hospital stay without any added risk. Journal of Paediatric Surgeons of Bangladesh (2019) Vol. 10 (1 & 2): 22-25